Solar photovoltaic power system for Bungin Island - Novi Azman; Rudi Naufal Fadhilah; Muhammad Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Bungin Island currently relies on diesel -based electricity power generation, resulting in limited supply reliability. This study evaluates the technical feasibility of an off-grid solar photovoltaic (PV) system integrated with lithium-ion battery energy storage (BESS) using photovoltaic system (PVsyst) simulation. Based on measured load demand of 2,830 kWh/day and NASA solar resource data, the optimized configuration consist of a 0.713 MWp PV array and an 11.54 MWh battery system. Simulation result indicates an annual PV production (E_Array) of 1,258.3 MWh/year. Of this, 1,032.9 MWh/year is delivered to the load, with excess energy of 120.84 MWh/year and a limited unmet load of 13.7 MWh/year (1.33%). The system achieves a solar fraction 98.67%, a performance ratio (PR) of 77.6% and a capacity factor of 17.34%. These results demonstrate that a properly sized PV-battery configuration can reliably replace diesel generation, providing a robust framework for high-renewable electrification in densely populated small islands.